Sanksi Tindak Pidana Pelecehan Dry-Humping Dalam Undang-Undang Nomor 12 Tahun 2022 Tentang Tindak Pidana Kekerasan Seksual Perspektif Hukum Pidana Islam - Moch Fajar Mubarok; Yusup Azazy; Deden Najmudin (AL-MUTSLA, 2025)
This article aims to examine the sanctions for the criminal act of dry humping sexual harassment based on Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence and the perspective of Islamic Criminal Law. Dry humping is a form of physical sexual harassment committed by rubbing the body on the victim's sensitive area without consent. This research uses a normative juridical method, with a statutory approach and a conceptual approach. Data is obtained through literature study of primary and secondary legal sources. The results showed that in Law Number 12 of 2022, the perpetrator of dry humping can be subject to a maximum imprisonment of four years and/or a maximum fine of fifty million rupiah as stipulated in Article 6. In addition, sanctions can be aggravated if committed under certain conditions as stipulated in Article 15. Meanwhile, in Islamic Criminal Law, this act is included in the category of despicable acts that are close to adultery and are subject to ta'zir sanctions, which are penalties determined by the judge. In conclusion, both positive law and Islamic Criminal Law recognize that dry humping is a form of physical sexual violence that must be sanctioned in order to protect the dignity of victims and maintain moral values in society.